Rola imienia we wczesnoszkolnym nauczaniu języków nierodzimych - Adryan, Karolina (Scripta Neophilologica Posnaniensia, 2020)
The article focuses on the effectiveness of the name-based method (Odimienna Metoda Nauki Czytania) developed by Irena Majchrzak in foreign language teaching to young pupils. Children’s names prove a good starting point for learning to read in a foreign language. As a valuable educational material of emotional charge, the name constitutes an integral part of the learner and thus can be used as a personalised primer containing a basic text to be the first read by children. Originally used to teach reading in Polish kindergartens, the name-based method may inspire teachers in teaching a foreign language to young learners as an ingenious pedagogical innovation. My professional experience indicates that the reading skills in a foreign language in the first stage of education are underestimated. My data come from a six-month experiment in a primary bilingual school where I introduced the name-based method. As a result, the children’s own names in their foreign language versions provided an excellent educational basis. The conclusions reveal that this method helps in expanding vocabulary, developing linguistic sensitivity, stimulating communication skills, and positively affecting language fluency.